Educational Administration and Management Student’s Conflict - Valverde Quirós, Magaly (2014)
This article analyzes the resolution of student conflicts in a public high school of the Costa Rican Ministry of Education – the Liceo de Paríso in the province of Cartago. The focus lies on how the administrative staff managed specific scenarios through a qualitative, phenomenological, investigational approach implemented at the school throughout 2014. Data is based on questionnaires, interviews and focus groups collected among the students, guidance counselors, the high school principal and staff. The research aims at determining the elements that characterize struggles among students at high schools - mainly verbal and physical conflicts. The paper looks at the most relevant causes and consequences for both the institution and the students, lack of programs to prevent such occurrences and daily planning by school administrators to counteract such encounters as well as raise awareness among the high school community.